Energetic adaptations persist after bariatric surgery in severely obese adolescents. (March 2015) - Butte, Nancy F.; Brandt, Mary L.; Wong, William W.; Liu, Yan; Mehta, Nitesh R.; Wilson, Theresa A.; Adolph, Anne L.; Puyau, Maurice R.; Vohra, Firoz A.; Shypailo, Roman J.; Zakeri, Issa F.
<x xml:space="preserve">Abstract</x> Objective Energetic adaptations induced by bariatric surgery have not been studied in adolescents or for extended periods postsurgery. Energetic, metabolic, and neuroendocrine responses to Roux‐en‐Y gastric bypass (RYGB) surgery were investigated in extremely obese adolescents. Methods At baseline and at 1.5, 6, and 12 months post‐baseline, 24‐h room calorimetry, body composition, and fasting blood biochemistries were measured in 11 obese adolescents relative to five matched controls. Results In the RYGB group, mean weight loss was 44 ± 19 kg at 12 months. Total energy expenditure (TEE), activity EE, basal metabolic rate (BMR), sleep EE, and walking EE significantly declined by 1.5 months (P = 0.001) and remained suppressed at 6 and 12 months. Adjusted for age, sex, fat‐free mass, and fat mass, EE was still lower than baseline (P = 0.001). Decreases in serum insulin, leptin, and triiodothyronine (T3), gut hormones, and urinary norepinephrine (NE) paralleled the decline in EE. Adjusted changes in TEE, BMR, and/or sleep EE were associated with decreases in insulin, homeostatic model assessment, leptin, thyroid stimulating hormone, total T3, peptide YY3‐36, glucagon‐like peptide‐2, and urinary NE and epinephrine (P = 0.001‐0.05). Conclusions Energetic adaptations in response to RYGB‐induced weight loss are associated with changes in insulin, adipokines, thyroid hormones, gut hormones, and sympathetic nervous system activity and persists 12 months postsurgery.